2020
DOI: 10.1186/s12906-020-02976-7
|View full text |Cite|
|
Sign up to set email alerts
|

Chemopreventive effect of Betulinic acid via mTOR -Caspases/Bcl2/Bax apoptotic signaling in pancreatic cancer

Abstract: Background: Pancreatic cancer is aggressive with no symptoms until the advanced stage reached. The increased resistance of pancreatic cancer to chemotherapy demonstrates a dilemma in the clinical field. Hence, it is a matter of great urgency to develop an effective drug to treat patients with pancreatic cancer. Betulinic acid is a major triterpene isolated from spina date seed. Several studies have suggested its low toxicity and side effects to patients with malaria and inflammation. However, relevant studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…Compounds extracted from plants belonging to diverse groups, for instance as alkaloids, flavonoids, as well as polyphenols, were explored for their anti-cancer influences, and potential data were obtained, thus providing a possible treatment approach for some human cancers [ 10 ]. Through the screening of these natural products, we have found that some natural products have strong anti-pancreatic cancer effects, such as Baohuoside 1 and betulinic acid, which may become effective agents for treating pancreatic cancer [ 11 , 12 ]. Fisetin (3,3’,4’,7-tetrahydroxyflavone), which distributes abundantly in vegetables, as well as fruits for instance cucumber, persimmon, and apple, was explored to possess antioxidant, anti-microbial, anti-cancer, as well as anti-inflammatory properties in recent studies [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compounds extracted from plants belonging to diverse groups, for instance as alkaloids, flavonoids, as well as polyphenols, were explored for their anti-cancer influences, and potential data were obtained, thus providing a possible treatment approach for some human cancers [ 10 ]. Through the screening of these natural products, we have found that some natural products have strong anti-pancreatic cancer effects, such as Baohuoside 1 and betulinic acid, which may become effective agents for treating pancreatic cancer [ 11 , 12 ]. Fisetin (3,3’,4’,7-tetrahydroxyflavone), which distributes abundantly in vegetables, as well as fruits for instance cucumber, persimmon, and apple, was explored to possess antioxidant, anti-microbial, anti-cancer, as well as anti-inflammatory properties in recent studies [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study suggested that the half maximal inhibitory concentration (IC 50 ) value of BA was 15 μg/mL in human lung cancer cells [ 57 ]. More recently, there is reported that the IC50 values of BA for pancreatic cancer PANC-1 cells and SW1990 cells were 21.5 μg/mL and 17.5 μg/mL, respectively [ 58 ]. Meanwhile, Hsu et al [ 59 ] demonstrated that the IC 50 values of BA was approximately 23 μg/mL in lung adenocarcinoma H1299 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Betulinic acid ( Figure 6 ) is a lupane-type pentacyclic triterpene that extensively spread throughout the plant kingdom. The recent studies that proved the activity betulinic acid possesses against cancer cells [ 43 , 44 ], especially melanoma [ 45 ], led to its selection by the National Cancer Institute for addition into the Rapid Access to Intervention in Development (RAID) program. Betulinic acid exhibits significant effects both in vitro ( Table 1 ) and in vivo ( Table 2 ) by manifesting cytotoxicity on various cancer cell lines and suppressing the growth of tumors.…”
Section: Natural Compounds Recognized As Chemotherapeutic Agentsmentioning
confidence: 99%